Electrochemical speciation analysis for simultaneous determination of Cr(iii) and Cr(vi) using an activated glassy carbon electrode. Issue 19 (20th July 2016) - Richtera, Lukas; Nguyen, Hoai Viet; Hynek, David; Kudr, Jiri; Adam, Vojtech
Abstract : In this study, the enhancement of electrochemical signals of Cr(iii ) and Cr(vi ) by using an activated glassy carbon electrode (GCE) measured by differential pulse voltammetry (DPV) is demonstrated. Abstract : In this study, the enhancement of electrochemical signals of Cr(iii ) and Cr(vi ) by using an activated glassy carbon electrode (GCE) measured by differential pulse voltammetry (DPV) is demonstrated. The activated GCE exhibited higher sensitivity for detection of Cr(iii ) and Cr(vi ) compared with the bare GCE. By using the activated GCE, the limit of detection decreased 15.3 times (from 0.230 to 0.015 μM) in the case of Cr(iii ) determination and 75 times (from 9.000 to 0.120 μM) in the case of Cr(vi ) determination. Moreover, a simultaneous speciation analysis of Cr(iii ) and Cr(vi ) using the activated GCE was presented. Scanning electron microscopy, elemental mapping, and electrochemical impedance spectroscopy were employed for investigation of the surface of the activated GCE. Finally, the influence of different ions (Na +, K +, NH4 +, SO4 2−, NO3 −, and Cl − in the form of Na2 SO4, NaNO3, NH4 Cl, and KCl salts) on the speciation signals of Cr(iii ) and Cr(vi ) in a mixture of the two Cr oxidation states was investigated.